2019
DOI: 10.1155/2019/1070495
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Potential of uPAR as a Biomarker in Renal Biopsies of Patients with FSGS

Abstract: Minimal change disease (MCD) and focal segmental glomerulosclerosis (FSGS) are primary glomerulopathies leading to proteinuria, known as podocytopathies, which share syndromic and morphological similarities. Morphological similarity occurs in cases of FSGS in which the sclerotic lesion was not sampled in renal biopsy, due to the focal nature of the disease. Differentiating these entities is very important, especially in cases of suspected FSGS but with sclerotic lesion not sampled, as they are diseases that ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The occurrence of FSGS is related to a variety of mechanisms. Podocyte injury is the central link of FSGS [16,17]. Glomerular sclerosis is the final pathological change in FSGS caused by the excessive accumulation of the glomerular extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of FSGS is related to a variety of mechanisms. Podocyte injury is the central link of FSGS [16,17]. Glomerular sclerosis is the final pathological change in FSGS caused by the excessive accumulation of the glomerular extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of DN was performed with three samples used for light microscopy (LM), direct immunofluorescence (IF) and transmission electron microscopy (TEM) according to the standard procedures [18].…”
Section: Renal Histopathologymentioning
confidence: 99%
“…Ultra-thin sections of 60 nm were prepared and placed in nickel grids. Sections were then stained with uranyl acetate and examined under a transmission electron microscope (EM-900; Zeiss, Germany) [18]. TEM was used to measure thickness of the glomerular basement membrane (GBM) and to exclude or identify renal diseases overlapping DN.…”
Section: Renal Histopathologymentioning
confidence: 99%
“…Previous results from our group have shown that podocytes have increased expression of urokinase plasminogen activator receptor (uPAR) in situ in biopsies from adult [ 8 ] and pediatric [ 9 ] patients with morphological lesions compatible with FSGS. From these findings, we evaluated the possible causes of cellular injury in podocytopathies.…”
Section: Resultsmentioning
confidence: 99%
“…For TEM, the sample was fixed with Karnovsky 2.5% + ruthenium red 0.2% and post-fixed in osmium tetroxide 2%, then dehydrated in graded alcohols and acetone solutions and embedded in Epon 812 resin. Ultrathin 60-nm-thick sections were cut and placed onto nickel grids and were subsequently contrasted with lead citrate 1% and uranyl acetate 3% and examined under an EM-900 transmission electron microscope (Zeiss, Germany) [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%